Digitalization of TQM: From Manual to Smart Quality System - Sastyawan, Murti; Ameliyana Rizky Syamara Putri Akhmad Yani; Zakiyan Zain Alkaf; Radita Dwi Putera; Tri Wisudawati (Jurnal Teknik Mesin Indonesia, 2025)
The digital transformation of Total Quality Management (TQM) represents a paradigm shift from traditional manual practices to data-driven, intelligent quality systems. This systematic literature review (SLR) examines the trajectory of TQM digitalization by analyzing 52 peer-reviewed articles published between 2011 and 2023. The review explores three main themes: (1) the transition from traditional to digital and intelligent quality tools; (2) the enablers and barriers to implementing digital TQM, including technological readiness, organizational culture, and data infrastructure; and (3) the evolving role of quality professionals in the era of Industry 4.0. Findings show that while automation and digital tools improve efficiency and decision-making, successful integration requires strategic alignment of human, technological, and managerial capabilities. The study also highlights gaps in empirical evidence regarding the long-term impact of smart quality systems on organizational performance. This review contributes to the understanding of digital quality transformation, and provides a conceptual framework to guide future research and practical implementation in quality management.